2005
DOI: 10.1111/j.1365-2125.2005.02389.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochromes P450 and MDR1 mRNA expression along the human gastrointestinal tract

Abstract: Br J Clin Pharmacol AimThe aim of this study was to quantify the mRNA expression of three cytochromes P450 (CYP) and P-glycoprotein (P-gp) in the human gastrointestinal (GI) tract. MethodBiopsies were obtained from gastric, duodenal, colonic and rectal mucosa during routine gastro-colonoscopy in 27 patients. The biopsies were snap-frozen in liquid nitrogen. Real-time reverse transcriptase-polymerase chain reaction (RT-PCR) was used for the quantitative analyses of mRNA expressed by the CYP2E1, CYP3A4 and CYP3A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
128
3
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(147 citation statements)
references
References 36 publications
13
128
3
3
Order By: Relevance
“…Initial disintegration of LCP-Tacro tablets has been shown to occur in the stomach and/or proximal small bowel but complete disintegration (and presumably optimal absorption) [41] occurs in the distal small bowel or the colon (FIGURE 2) [34]. There appears to be less gut CYP3A4 activity in the distal portions of the gastrointestinal system [42] and thus less pre-systemic metabolism of tacrolimus, resulting in lower clearance and further increased bioavailability.…”
Section: Pks and Metabolismmentioning
confidence: 99%
“…Initial disintegration of LCP-Tacro tablets has been shown to occur in the stomach and/or proximal small bowel but complete disintegration (and presumably optimal absorption) [41] occurs in the distal small bowel or the colon (FIGURE 2) [34]. There appears to be less gut CYP3A4 activity in the distal portions of the gastrointestinal system [42] and thus less pre-systemic metabolism of tacrolimus, resulting in lower clearance and further increased bioavailability.…”
Section: Pks and Metabolismmentioning
confidence: 99%
“…In that study, we found that the magnitude of mdr1a mRNA was in the order of ileum > jejunum > duodenum, while that of CYP3A mRNA was in the opposite order; further, of cyclosporin A under physiological conditions, whereas after induction by dexamethasone induced these mRNAs more strongly in the intestinal regions where expression was weaker in untreated animals. Thorn et al [33] reported regarding the expression of CYP and mdr mRNAs along the human gastrointestinal tract. Then, the pattern of expression of these mRNAs in duodenum, jejunum and ileum of human was well similar to those of our mice.…”
Section: Discussionmentioning
confidence: 99%
“…The conditions for PCR were as follows: 94 °C predenaturation for 5 min, 94 °C denaturation for 30 s, 56 °C annealing for 30 s, 72 °C extension for 1 min followed by 72 °C 10 min for 35 cycles. Aliquots of the PCR product were electrophoresed on 1.5% agarose gels and PCR fragments were visualized by UV illumination (UVP GDS7500 Gel, Upland, CA, USA) stained by ethidium bromide (Thörn et al 2005). The fl uorescence intensity of β-actin fragments served as the criterion for the MDR1 fragments.…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%